Amylase inhibitors and their biomedical applications. Issue 7 (18th March 2013) - Jayaraj, Sujatha; Suresh, Sukrutha; Kadeppagari, Ravi‐Kumar; Tester, Richard F.
Abstract Amylases are a class of enzymes that hydrolyze starch to yield low molecular weight dextrins and sugars and they play important role in the digestion of carbohydrates. Inhibition of α‐amylase along with α‐glucosidase can significantly reduce the post‐prandial increase of blood glucose and can be an important strategy in the control of blood glucose level in the type‐2 diabetic patients. Hence, pancreatic α‐amylase and gastric glucoamylases are the major therapeutic targets for the type‐2 diabetes mellitus. Amylase inhibitors are already in the market for the treatment of diabetes. Amylase inhibitors can also be used for controlling obesity. In addition to medical applications, amylase inhibitors help in the control of pests. Therefore, amylase inhibitors play an important role in the pest management. Hence, this review is focused on the biomedical applications of amylase inhibitors. In addition, sources, different types, inhibition mechanisms, and molecular aspects of amylase inhibitors are discussed.